Learning outcomes for early childhood development in the Caribbean : a handbook for practitioners (UWI. Chalkboard Press KingstonJM, 2010)
provides practical and informed guidance for early childhood practitioners in support of the acknowledged regional imperative to give its young Caribbean citizens the best possible start in life. Draws on research evidence evidence on the developing child and practical programming experience in day care and preschool settings, which demonstrated emphatically the positive impact of quality early childhood interventions on both cognitive and affective outcomes.
Keywords: EDUCATION